Always Different, Always the Same: Critical Essays on The Fall - Devereux, Eoin; Power, Martin J. (Rowman & Littlefield Publishers, 2022)
The Fall, led by Mark E. Smith, were one of the most intriguing, influential, and prolific post-punk groups in British popular culture. Always Different, Always the Same: Critical Essays on The Fall is a thorough and critical account of the group, engaging with the often complex and challenging creative work. In this groundbreaking text, volume editors Eoin Devereux and Martin J. Power bring together contributions from a wide variety of disciplinary homes, including ethnomusicology, sociology, literary theory, linguistics, journalism, cultural studies, and film and media studies. Contributors Kieran Cashell, Brian Clancy, Matt Davies, Eoin Devereux, Samuel Flannagan, John Fleming, Gavin Friday, Mike Glennon, K. A. Laity, Ben Lawley, John McFarland, David Meagher, Michael Mary Murphy, Martin Myers, Martin J. Power, Suzanne Smith, Elaine Vaughan, Paul Wilson.